Recent advances in sustainable technologies select proceedings of ICAST 2020 - Jha, Kanishka; Gulati, Piyush; Tripathi, Uma Kant (Lecture Notes in Mechanical Engineering, 2021)
This book presents select proceedings of the International Conference on Advances in Sustainable Technologies (ICAST 2020), organized by Lovely Professional University, Punjab, India. The topics covered in this book are multidisciplinary in nature. The primary topics included in the book are from the domains of automobile engineering, mechatronics, material science and engineering, aerospace engineering, bio-mechanics, biomedical instrumentation, mathematical techniques, agricultural engineering, nuclear engineering, physics, biodynamic modelling and ergonomics etc. The contents of this book will be beneficial for beginners, researchers, and professionals alike.